The Global Trends of Research on Records Management: A Bibliometric Analysis - Muhammad Karfa Bizi; Asmadi Mohammed Ghazali; Mohd Nizam Bin Yunus; Moh. Safii (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2026)
Background of the study: The records management field has grown with the rise of digital records, information governance, and emerging technologies. However, its global trends have not been fully mapped, especially through bibliometric analysis. Thus, an updated study is required to scrutinize the growth of publications, research influence, and key themes in this field. Purpose: This study provides a path to the intellectual and thematic evolution of records management, charting key authors and emerging themes that drive research questions. Method: A bibliometric study using 1100 Scopus-indexed publications on records management from 1949 to 2024, based on criteria such as journal impact, researcher productivity, institutional contributions, and emerging trends. Descriptive performance of documents was measured using metadata, including annual productivity, document and source types, languages, subject areas, countries, institutions, and authors; citation metrics included total citations and h-index. Network mapping was performed in VOSviewer to examine co-authorship and co-occurrence of author keywords. Findings: The literature grew rapidly after the late 1990s and peaked in 2023. Most publications are in English. Records management research is mainly linked to Social Sciences (28.32%), followed by Computer Science (19.48%) and Business, Management and Accounting (12.54%). The United States, the United Kingdom, India, and Malaysia are the leading contributors. Keyword analysis shows continuing interest in core records management, with growing focus on blockchain, security, and health records. Conclusion: The evidence suggests that records management is becoming more interdisciplinary and technology-driven, especially in digital governance, security, healthcare records, and blockchain. Future studies should practice multiple databases and examine these emerging themes in greater depth.